Pediatric gastric trichobezoars with acute life threatening and undifferentiated elective bipolar clinical presentations - Amit Kumar Sinha; Maheshkumar Manilal Vaghela; Bindey Kumar; Prem Kumar (Elsevier, 2017)
Trichobezoar is a rare clinical condition causing acute abdomen in children. Clinical presentation is varied and ranging from chronic abdominal pain to gastric perforation. Its early diagnosis is necessary to combat complications. We are presenting two cases of gastric trichobezoars showing two poles of clinical presentation-chronic undifferentiated one and acute life threatening with perforative peritonitis.